A behavioral model for optically powered OCT endoscope with a micro electrostatic vertical‐comb optical scanner. Issue 4 (23rd May 2014) - Nakada, Muneki; Chong, Changho; Morosawa, Atsushi; Isamoto, Keiji; Suzuki, Takuya; Fujita, Hiroyuki; Toshiyoshi, Hiroshi
<x xml:space="preserve">Abstract</x> This paper presents a novel device architecture for optically actuated microelectromechanical systems (MEMS) endoscopes for optical coherence tomography (OCT) measurement. A 10‐mW infrared light beam at a wavelength of 1.5 µm is transferred through the single‐mode fiber to provide a scanning MEMS mirror with the drive voltage (maximum 11 V) by exciting a photovoltaic cell, while also providing with a secondary light beam at a wavelength of 1.3 µm for the OCT measurement. An electrostatic vertical comb‐drive optical scanner (1.5 mm × 2.0 mm × 0.5 mm) has been developed by using the deep reactive ion etching (DRIE) of a silicon‐on‐insulator (SOI) wafer. The design of the scanner module is discussed, along with the experimental results of electrostatic operation. An equivalent circuit model for the optical scanner is developed to explain the behavior of the optically powered actuation mechanism, including the hysteresis loop in the frequency response and the voltage dependence of oscillating angle (mechanical peak ±3.2°/7 V around the resonance frequency of 250 Hz). OCT measurement of a tissue is demonstrated to reconstruct the cross‐sectional image of a fingerprint at a resolution of lateral 40 µm × vertical 8 µm and penetration depth of 2.5 mm. © 2014 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.